Association between birth order and emergency room visits and acute hospital admissions following pediatric vaccination: a self-controlled study. - Steven Hawken; Jeffrey C Kwong; Shelley L Deeks; Natasha S Crowcroft; Robin Ducharme; Douglas G Manuel; Kumanan Wilson (PLoS ONE, 2013)
OBJECTIVE: We investigated the association between a child's birth order and emergency room (ER) visits and hospital admissions following 2-,4-,6- and 12-month pediatric vaccinations. METHODS: We included all children born in Ontario between April 1(st), 2006 and March 31(st), 2009 who received a qualifying vaccination. We identified vaccinations, ER visits and admissions using health administrative data housed at the Institute for Clinical Evaluative Sciences. We used the self-controlled case series design to compare the relative incidence (RI) of events among 1(st)-born and later-born children using relative incidence ratios (RIR). RESULTS: For the 2-month vaccination, the RIR for 1(st)-borns versus later-born children was 1.37 (95% CI: 1.19-1.57), which translates to 112 additional events/100,000 vaccinated. For the 4-month vaccination, the RIR for 1(st)-borns vs. later-borns was 1.70 (95% CI: 1.45-1.99), representing 157 additional events/100,000 vaccinated. At 6 months, the RIR for 1(st) vs. later-borns was 1.27 (95% CI: 1.09-1.48), or 77 excess events/100,000 vaccinated. At the 12-month vaccination, the RIR was 1.11 (95% CI: 1.02-1.21), or 249 excess events/100,000 vaccinated. CONCLUSIONS: Birth order is associated with increased incidence of ER visits and hospitalizations following vaccination in infancy. 1(st)-born children had significantly higher relative incidence of events compared to later-born children.